A detailed quantum mechanical and quasiclassical trajectory study on the dynamics of the H++H2?H2+H+ exchange reaction - González-lezana, Tomás; Roncero, Octavio; Honvault, Pascal; Launay, Jean-Michel; Bulut, Nlyazl; Aoiz, F.Javler; Bañares, Luis (My University, 2006)
The H++H2 exchange reaction has been studied theoretically by means of a different variety of methods as an exact time independent quantum mechanical, approximate quantum wave packet, statistical quantum, and quasiclassical trajectory approaches. Total and state-to-state reaction probabilities in terms of the collision energy for different values of the total angular momentum obtained with these methods are compared. The dynamics of the reaction is extensively studied at the collision energy of Ecoll=0.44 eV. Integral and differential cross sections and opacity functions at this collision energy have been calculated. In particular, the fairly good description of the exact quantum results provided by the statistical quantum method suggests that the dynamics of the process is governed by an insertion mechanism with the formation of a long-lived collision complex. © 2006 American Institute of Physics.
Keywords: Functions; Hydrogen; Ion exchange; Opacity; Reaction kinetics; Statistical methods; Angular momenta; Collision energy; Quantum wave packets; Statistical quantum trajectory approach; Quantum theory